Upaya Meningkatkan Prestasi Belajar IPS dengan Menggunakan Metode Kerja Kelompok pada Siswa Kelas IV SD N Gading Asri, Playen, Gunungkidul Tahun Pelajaran 2021/2022 - Sri Muryanti; Sukadari Sukadari (UM Purwokerto Press, 2022)
The background of this research is that the lack of social studies learning achievement is caused by the selection of learning methods that do not increase students' motivation and activeness in participating in learning. Given that the learning process is very large in determining the success of students, it is necessary to conduct research on learning improvements. The purpose of this study is to prove that the application of the group work method can improve student learning achievement regarding the material for maintaining personal documents and valuables for fourth grade students at SDN Gading Asri, Playen, Gunungkisul, Academic Year 2021/2022. The research was carried out in 2 cycles consisting of cycle 1 on 20 and 22 August 2021. then cycle 2 will be held on 27 and 29 August 2021. Each cycle consists of several stages, namely: planning, implementation, observation and reflection. The data collected is analyzed at each stage of the cycle with quantitative descriptive analysis. Based on the research results, it can be concluded that the improvement of learning through the group work method in social studies subjects for fourth grade students at SDN Gading Asri in the 2021/2022 academic year can be increased. This can be seen from the increase in the average score of students starting from pre-cycle activities, namely 66, after the action in the first cycle increased to 73 then after the second cycle of action the average value increased again to 84.